ANTI-INFLAMMATORY ACTIVITY OF BACTERIA ASSOCIATED WITH MARINE SPONGE (HALICLONA AMBOINENSIS) VIA REDUCTING NO PRODUCTION AND INHIBITING CYCLOOXYGENASE-1, CYCLOOXYGENASE-2, AND SECRETORY PHOSPHOLIPASE A2 ACTIVITIES - Andriani, Yosie; Marlina, Leni; Mohamad, Habsah; Amir, Hermansyah; Radzi, Siti Aisha M; Saidin, Jasnizat (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study aimed to investigate the anti-inflammatory activity of methanol extract and fractions of bacteria associated with sponge (Haliclona amboinensis) and to evaluate their effect in reducing NO production and inhibiting cyclooxygenase-1 (COX-1), cyclooxgenase-2 (COX-2) and secretory phospholipase A2 (sPLA2) activity. Methods: All bacterial isolates were cultured and supernatants were collected for the extraction of secondary metabolites using diaion HP-20 to obtain methanol extracts. Evaluation of cytotoxicity property was carried out on macrophage cell lines (RAW264.7) by 3-(4,5-dimethylthiazol- 2-yl) 2,5-diphenyl tetrazoliumbromide assay. Anti-inflammatory screening was done by inducible nitric oxide assay on RAW264.7 cell lines with lipopolysaccharide (LPS) stimulation. Dianion HP-20 was used to remove salt content. A selected methanol extract was subjected to further fractionations by C-18 reverse phase and their anti-inflammatory potential was evaluated by COX-1 and COX-2, and sPLA2 enzymatic assay. Results: Seven methanol extracts showed no cytotoxic property against RAW 264.7 cell line (inhibitory concentration 50% > 30 Î¼g/ml) and selected for anti-inflammatory screening assay. Result showed methanol extract HM 1.2 reduced NO production >80% and it has been selected for phytochemical screening, further fractionations and assay. Phytochemical screening showed alkaloids and terpenoids present in the HM 1.2. The HM 1.2 and its fractions (F1, F2, F1C1, F1C2, F1C3, and F1C4) were proven to inhibit COX-1, COX-2, and sPLA2 activity in the range of 60.516-116.886%, 20.554- 116.457%, and 70.2667-114.8148%, respectively. Conclusions: This study revealed that bacteria associated with H. amboinensis have produced anti-inflammatory activity via reducing NO production and inhibiting COX-1, COX-2, and sPLA2 activity. Â